Influences on risk taking behaviour of property developers in Perth, Western Australia - Baccarini, David; Kraus, F. (TBA, 2005)
Risk is inherently part of the process of property development so property developers are driven to engage in risk taking behaviour. This paper investigates project developers' perception of influences on their risk taking behaviour of small-scale residential developments in Perth (Western Australia) based on structured interviews with twenty property developers. It was found that property developers perceive risk-taking behaviour is influenced by the risk level in projects in terms of the degree of variability of outcomes and/or magnitude of potential losses. Property developers expressed a strong risk averse attitude, which means risk-taking behaviour is influenced by the desire to not engage in projects where risks greatly exceed to rewards; in fact, many seek out developments where the rewards disproportionately exceed the risks because risk and reward are seem as not necessarily being related. 11iese potential rewards and risks tend to be framed opportunistically, which suggest that rewards are likely to be more emphasised than risks. Property developers seem to be particularly prone to availability bias, which means their risk-taking behaviour may result in irrational decisions based on irrelevant information. All these influences on risk-taking behaviour - level of risk, risk averse attitude and opportunistic framing - are tempered by a personality trait that promotes proper planning and problem-solving when involved in risk-taking behaviour. Finally, it must be emphasised that this research is based on project developers' perceptions of their own behaviour and provides a foundation for further observational or experimental research to compare these perceptions with actual risk taking behaviour.